Prescribing Patterns in a Primary Care Service in a Rural Site in the Philippines from April 2019 to March 2020 – A Cross-sectional Study - Lanip, Nicole Andrea C. (Archīum Ateneo, 2024)
Background Appropriate use of medication is an important indicator of quality healthcare delivery among children. Previously published studies on drug utilization involved Filipino households in general and were conducted in the 1990s. No recent Philippine studies have been conducted that focus on drug utilization in children. Objective To describe the current prescribing patterns in one primary care service in a rural site in the Philippines using the World Health Organization (WHO) prescribing indicators. Methods A cross-sectional study was conducted by review of electronic medical records of patients seen at the primary care facility under the Philippine Primary Care Studies (PPCS) rural site from April 2019 to March 2020. Out of 9,930 total encounters, 623 patient encounters with prescriptions for pediatric patients were included in the study through systematic sampling. The average number of drugs per encounter, percentage of drugs prescribed by their generic names, percentage of encounters with prescribed antibiotics, percentage of encounters with prescribed injections, and percentage of drugs prescribed from the Philippine Drug Formulary were calculated. Values were compared to the cut-offs considered “good practice” for outpatient care in the WHO manual: (1) an average number of less than two drugs per encounter; (2) less than 30% of encounters are prescribed with antibiotics; (3) less than 20% of encounters are prescribed with injections; (4) 100% of drugs are prescribed by generic name; and (5) 100% of drugs are from the formulary. Results On the average, three drugs were prescribed per encounter. Most patient encounters (80.9%) involved antibiotics prescription — higher than the WHO standard value of 30%. All drugs were prescribed by generic name and were prescribed from the formulary. Only 0.5% of encounters were prescribed injections, all of which were administered through the intramuscular route. Of the 1,962 prescriptions generated, antibiotics was the most prescribed medication (25.7%). The most common diagnosis was infectious in nature (88.8%). Conclusion The primary care service achieved the WHO standard values in terms of prescribing by injections and by generic names. There was a high rate of antibiotic prescriptions at 83%, and a high average number of drugs prescribed per encounter, exceeding the WHO standard value.